(untitled) (AYUSHDHARA, 2020)
Dysmenorrhea is the most common gynecological problem faced by women during their adolescence and also in reproductive age which causes significant discomfort and anxiety for the women. In modern medicine dysmenorrhea is treated by oral contraceptive pills, non-steroidal anti-inflammatory drugs, antispasmodic, analgesics etc. This treatment may relieve symptoms of dysmenorrhoea but it does not address the root of the problem. Long term use of these causes side effects. So to minimize these complications, an attempt is made to find out safe, potent, cost effective remedy from Ayurveda for the management of Kashtartava. In Ayurveda Kashtartava, term which is being used for the condition where in a women may suffer with pain during menstruation. Pain is the main feature of Kashtartava, so it has strong relation with Vata Dosha. For the management of this vitiated Vata, treatment that effect direct on the place of Vata should be selected therefore by administering Basti to normalize vitiation of Vata and proper measures to correct the Agnivikara should be the prime objectives of the treatment. Keeping this point in view, the present clinical trial, a clinical study to evaluate efficacy of “Trivritadi Taila Anuvasan-Basti” in the management of Kashtartava with special reference to Primary Dysmenorrhea was taken. Trivritadi Taila Anuvasan-Basti due to the properties of Anulomana and Vatahara may it effectively brings down the Pratiloma Gati Vata which is mentioned in A.S.Utt. 39/29 for Udavartini Yonivyapad, which is one of the main disease conditions compares with Kashtartava (Primary dysmenorrhoea). Results were assessed on the basis of improvement in the subjective parameters. The study reveals that patients of Kashtartava after treatment showed significant improvement in chief complaints, from the above trial it is clear that Trivritadi Taila Anuvasan-Basti can be used as a safe and effective therapeutic agent in the management of Kashtartava.